IMPLEMENTASI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MTS HIDAYATUS SALAM GRESIK - Ilvi Nurdiyanah; Ika Ratih Sulistiani; Arief Ardiansyah (VICRATINA, 2021)
Contextual Teaching and Learning Approach is one of implemented approaches in Hidayatus Salam Islamic Junior High School. That institution is one of private schools placed in a village. Many factors have affected the students, especially religion. So, the teachers apply this kind of approach so that all students can easily comprehend the material and implement it. The goal of this research is to find out the implementation of contextual approach in learning Islamic study and the influencing factors. This research uses qualitative descriptive method in form of case study. The data resource of this research is the headmaster of the school, the deputy head of curriculum, the Islamic teacher, and the students. The implementation of contextual approach in Hidayatus Salam Islamic Junior High School runs well. The Islamic teacher has applied the approach as the aspects and components. the factors are: a. The class atmosphere really supported, b. The students extremely enthused in learning, c. There was learning media. The retardation factors are: a. There were still Islamic teachers who had less understanding about contextual approach theories, b. The students' cognitive aspects were unstable, c. Lesson time is minus.